PERAN SISTEM INFORMASI MANAJEMEN ORGANISASI DALAM PENGAMBILAN KEPUTUSAN - Andrian Syahputra; Ragil Wiranti; Widiya Astita, Widiya Astita (Jurnal Manajemen Sistem Informasi (JMASIF), 2022)
Management information systems provide accurate and timely information needed to facilitate the decision-making and problem-solving processes that enable the implementation of planning, control and operational functions to run effectively. The approach in scientific writing uses a qualitative descriptive method. The results of this study indicate that the development and management of MIS in an organization is able to trigger decisions that are not only fast and accurate but will also be in line with the best practices in the organization effectively and efficiently. Information has become an important source for managing modern organization.